HUBUNGAN POLA MAKAN, AKTIVITAS FISIK DAN INTENSITAS PENGGUNAAN MEDIA SOSIAL DENGAN STATUS GIZI LEBIH PADA REMAJA DI SMA NEGERI 14 JAKARTA TIMUR - Afifah Azzahra, (2020)
Adolescence is a second important period in a life that has transitioning physical, psychic, social, and nutritional needs from children to adults. Nutritional problems often found today are more nutritional problems due to an imbalance between feeding and energy expenditure through physical activity. The habit of spending time to access social media when done more than two hours to be one of the overnutrition status risk factors in adolescents. This study aimed to determine the correlation between eating pattern, physical activity and the intensity of using social media with overnutrition status in adolescents at SMAN 14 East Jakarta. This study used cross sectional design with chi square test method. Eating pattern using SQ-FFQ, physical activity using PAL, intensity of using social media using SONTUS and anthropometry measurements included weight and height for 58 adolescents. The results of the analysis showed that the eating pattern (p=0,014), the physical activity (p=0,023) and the intensity of using social media (p=0,000) had a correlation to the overnutrition status in adolescents (p<0,05). This shows that there was a correlation between eating pattern, physical activity and intensity of using social media with overnutrion status in adolescents at SMAN 14 East Jakarta.